The effect of gait training and exercise programs on gait and balance in post-stroke patients - Mochizuki,Luis (2015)
The aim of this review is to evaluate studies about gait training and exercise interventions applied to patients following chronic stroke on gait and balance. The studies included in this review were random clinical trials, including only chronic post-stroke individuals that evaluated gait and balance outcomes and with a PEDro scale score ≥ 7.0. Eight studies were selected. The results suggest gait and balance will only be affected in chronic post-stroke patients if training sessions last at least 30 minutes, are repeated three times a week, and maintained for at least five weeks. Gait training affects how chronic post-stroke individuals walk. They will probably walk faster and with a lower risk of falling; however, it is unclear whether the consequences of these procedures affect the quality of life.